2019
DOI: 10.1111/cns.13230
|View full text |Cite
|
Sign up to set email alerts
|

Anhedonia across borders: Transdiagnostic relevance of reward dysfunction for noninvasive brain stimulation endophenotypes

Abstract: Introduction Anhedonia is a transdiagnostic psychopathological dimension, consisting in the impaired ability to experience pleasure. In order to further our understanding of its neural correlates and to explore its potential relevance as a predictor of treatment response, in this article we systematically reviewed studies involving anhedonia and neuromodulation interventions, across different disorders. Methods We included seven studies fulfilling inclusion/exclusion criteria and involving different measures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 73 publications
0
26
0
Order By: Relevance
“…The effectiveness of rTMS in healthy models compares with human studies involving non-depressed patients and healthy subjects. For example, left human DLPFC stimulation has been demonstrated to reverse hedonic tone dysfunction in addicted subjects 62 , as well as to induce a more pronounced sensitivity to rewarding stimuli in healthy subjects 63,64 . Also, rTMS appeared to selectively reverse depressive-like symptoms while effects on other domains (e.g., anxiety) were rather mixed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of rTMS in healthy models compares with human studies involving non-depressed patients and healthy subjects. For example, left human DLPFC stimulation has been demonstrated to reverse hedonic tone dysfunction in addicted subjects 62 , as well as to induce a more pronounced sensitivity to rewarding stimuli in healthy subjects 63,64 . Also, rTMS appeared to selectively reverse depressive-like symptoms while effects on other domains (e.g., anxiety) were rather mixed.…”
Section: Discussionmentioning
confidence: 99%
“…Stress models of depression, while well-validated in preclinical research, encompass a broad array of symptoms thus possibly diluting specific target treatment effects and introducing bias when examining biological changes associated with rTMS. Narrower phenotypes may capture the biological effects of rTMS and improve prediction of treatment response 63 . The DSM-5 definition of MDD likely represents an aggregate of different and probably highly diverse disease subtypes, each of which should be studied independently and might require specific therapeutic strategies 76 .…”
Section: Discussionmentioning
confidence: 99%
“…The former represents the inability to experience pleasure or interest in almost all activities of daily life and seems to be a transdiagnostic dimension which is not only interesting for studies on MDD [37]. The latter consists of negative expectations about the future, which could involve the self and others, where subjects find it impossible to solve their problems, so that they never reach their life goals [3].…”
Section: Discussionmentioning
confidence: 99%
“…Spano et al suggest that anhedonia may be a "transdiagnostic psychological dimension" and speculates that the presence of anhedonia may indicate a predisposition to respond to TMS treatment [6]. We cannot comment on these broader points but provide important information on anhedonia in MDD.…”
Section: Discussionmentioning
confidence: 80%
“…Spano et al suggested anhedonia as a "transdiagnostic psychopathological dimension", which may respond to non-invasive brain stimulation (NIBS) [6]. They also suggested that when anhedonia is a core feature of a mental disorder, this may indicate the parent disorder will respond to NIBS.…”
Section: Introductionmentioning
confidence: 99%